Effects of Postpartum Hemorrhage Prevention Program on Postpartum Blood Loss and Outcomes of Labor among Low Risk Nulliparous Women - Thongnat, Waraporn; Siriarunrat, Supit; Tachasuksri, Tatirat (Journal of Phrapokklao Nursing College, Chanthaburi, 2021)
This quasi-experimental research aimed to study the effects of postpartum hemorrhage prevention program on postpartum blood loss and outcomes of labor among low risk nulliparous women. The participants consisted of 54 low risk nulliparous women giving birth in delivery room at a general hospital in Chonburi Province and were equally divided into an experimental group (n = 27) and a control group (n = 27). The research instruments comprised a postpartum hemorrhage prevention program, a demographic and pregnancy record form, and a labor record form. The implementation and data collection were conducted from October, 2018 to July, 2019. Data were analyzed by frequency, percentage, mean, standard deviation, independent t-test, Chi-square test, Mann-Whitney U test, and Fisher’s exact test. The research results revealed that there were no differences of mean postpartum blood loss, duration of the first stage of labour, duration of the second stage of labour, and the degree of perineal tear between the experimental group and the control group. This research suggests that labour nurses should apply this postpartum hemorrhage prevention program in caring for low risk parturients especially promoting the open glottis method and restricting episiotomy in order to decrease the degree of perineal tear.